Biological properties of a thermally crosslinked gelatin film as a novel anti‐adhesive material: Relationship between the biological properties and the extent of thermal crosslinking. Issue 7 (29th November 2014) - Tsujimoto, Hiroyuki; Tanzawa, Ayumi; Miyamoto, Hiroe; Horii, Tsunehito; Tsuji, Misaki; Kawasumi, Akari; Tamura, Atsushi; Wang, Zhen; Abe, Rie; Tanaka, Shota; Yamanaka, Kouki; Matoba, Mari; et al.
Abstract: In order to prevent postoperative adhesion and the related complications, a thermally crosslinked gelatin (TCG) film was developed and the basic biological properties were examined, paying special attention to the relationship between these properties and the extent of crosslinking of the film. The gelatin films crosslinked thermally for five different time periods (0, 1, 3, 8, and 14 hours) were developed and the following tests were performed. Regarding the material characterization of the films, the water content, the water solubility, and the enzymatic degradation for collagenase were found to be closely related to the duration of thermal crosslinking. In an in vitro study conducted to examine the cell growth of fibroblasts cultured on the films, the degree of cell growth, except no crosslinked film, was less than that observed in the control group, thus suggesting that such effects of the films on fibroblast cell growth may be related with their anti‐adhesive effects. In in vivo tests, the films crosslinked for longer time periods (3, 8, and 14 hours) were retained for longer after being implanted into the abdominal cavity in rats and showed a significant anti‐adhesive effect in the rat cecum adhesion models, indicating that the biodegradability and anti‐adhesive effects of the TCG films depend on the duration of thermal crosslinking. In order to develop useful and effective anti‐adhesive gelatin film, it is very important to optimize duration of the thermal crosslinking. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1511–1518, 2015.